Reversing the trend of weak policy implementation in the Kenyan health sector? - a study of budget allocation and spending of health resources versus set priorities - Maina Thomas M; Glenngård Anna H (BMC, 2007)
Abstract Background Policy implementation in the context of health systems is generally difficult and the Kenyan health sector situation is not an exception. In 2005, a new health sector strategic plan that outlines the vision and the policy direction of the health sector was launched and during the same year the health sector was allocated a substantial budget increment. On basis of these indications of a willingness to improve the health care system among policy makers, the objective of this study was to assess whether there was a change in policy implementation during 2005 in Kenya. Methodology Budget allocations and actual expenditures compared to set policy objectives in the Kenyan health sector was studied. Three data sources were used: budget estimates, interviews with key stakeholders in the health sector and government and donor documentation. Results Budget allocations and actual expenditures in part go against policy objectives. Failures to use a significant proportion of available funds, reallocation of funds between line items and weak procurements systems at the local level and delays in disbursement of funds at the central level create gaps between policy objectives and policy implementation. Some of the discrepancy seems to be due to a mismatch between responsibilities and capabilities at different levels of the system. Conclusion We found no evidence that the trend of weak policy implementation in the Kenyan health sector was reversed during 2005 but ongoing efforts towards hastening release of funds to the districts might help solving the issue of low absorption capacity at the district level. It is important, however, to work with clear definitions of roles and responsibilities and well-functioning communications between different levels of the system.